The performance of an improved gas cleaning system for the continuous operation of a rice husk downdraft gasifier - Buenaventura, Ramon M. (1999)
This paper is an experimental study on the performance of an improved gas cleaning system for the continuous operation of a rice husk downdraft gasifier. This study also includes the gasification of rice husk, and the effects of the producer gas on the diesel engine. Producer gas-fueled system utilizing rice husk offers an attractive alternative to fossil-fueled power units due to its abundance in developing countries. This is especially useful to farmers and rice mills operating in the countryside where fossil fuel is not readily available.
In this study, the existing gasifier set-up of the Mechanical Engineering Laboratory of the University of the Philippines was used and modified to provide producer gas for the diesel engine generator. Particular emphasis was given to the practical aspects of the gasifier-engine-generator system operations and maintenance procedure. Engine speed settings of 800 to 1800 revolutions per minute and load settings of 10 to 60 Amperes were used.
The results showed that the gasifier-engine-generator system is a viable alternative power source. It was able to operate continuously for 4 hours, limited only be the capacity of the ash bin. It accumulated a total of 105 hours of operation with no harmful effects on the diesel engine as shown by the results of its engine oil analysis. It also showed that the designed gas cleaning system, including the oil bath, is effective in cleaning the producer gas as evidenced by its tar and particulate contents of less than 2 mg per m^3 of product gas.
Thesis (M.S. Mechanical Engineering)--University of the Philippines, Diliman.
Keywords: Gases -- Cleaning; Rice hulls as fuel